Analysis of Self-excited Damage and System Design for High-power Variable Frequency Power Supply in Overspeed Region - JIANG Ping; MEI Wenqing; GAN Weiwei; ZHOU Zhiyu; HU Xian; ZHOU Rong (Kongzhi Yu Xinxi Jishu)
Owing to the phenomenon that the converter with LC filter has been suffered fault shut-down in overspeed test and then resulted in damage of power devices, the simulation analysis and experimental verification were both carried out. Combing simulation and experimental results, the theoretical analysis of self-excitation between asynchronous and filter capacitor was completed, and the system design to remove the filter capacitor in overspeed region was proposed. Simulation and experiment results show that the scheme is feasible.